Ancient restoration and production technologies of Roman mortars from monuments placed in hydrogeological risk areas: a case study - Sitzia, Fabio (2022)
This paper focuses on the study of different Roman mortars (renders, finishing coats), used in the construction and restoration of the Forum Traiani thermal baths (Central Sardinia, Italy), a significant example of the Roman-style architecture in Sardinia. The archaeological site is located in a high hydrogeological risk area, due to the cyclical flooding of nearby Tirso river. Moreover, the presence of thermal saline (NaCl-bearing) water spring directly in contact with mortars and building stones, also contributed to structure degradation. An analytical approach, comprising mineralogical-petrographic characterization, physical analysis and particle-size distribution of aggregate, was used for mortars characterization. In addition, pXRD analysis on mortars defined the presence of alteration minerals while the thermal characterization (TGA) gave information about binder hydraulicity degree. Further μ-XRD-associated μ-Raman spectroscopy and μ-FTIR were utilized for pigments identification on frescos. Interesting results came from two wall stratigraphic series of mortars, highlighting construction stages, ancient restoring interventions and waterproofing methods. The main pigments used on red, yellow and black frescoes were red ochre, goethite and wood charcoal respectively.